Analisis Efektivitas Komunikasi Tulis Baca Konfirmasi dalam Sasaran Keselamatan Pasien di Ruang Rawat Inap Rumah Sakit X Jepara - Sinta Nurani; Sudiro Sudiro (Jurnal Manajemen Kesehatan Indonesia, 2019)
Communication is one of the root causes of mismanagement of medical actions, lack of division of labor and coordination between professions as one of the cultural barriers to safety enforcement in hospitals. Hospitals must have a list of permitted or prohibited abbreviations which can often lead to fatal communication errors. Doctors in private hospitals in regions such as the "X" Jepara hospital come from government hospitals, especially specialist doctors. The time that doctors give very little to meet patients and talk with nurses about the patient's health status is also a problem for patient care. General Purpose: To analyze the implementation of communication TBK in an effort to prevent events related to patient safety.This study uses data collection methods through indepth interviews (in-depth interviews) with informants who have been selected and determined in relation to the implementation of the communication process of effective inpatient installation of Jepara X Hospital. Data processing is carried out with four main processes of qualitative data analysis, namely comprehending, synthesizing, theorizing and recontextualizing.The results of the study show the implementation of communication TBK in an effort to prevent events related to patient safety Application of effective communication requires a confirmation sheet as proof of recording. But this is not yet available at the X Hospital in Jepara. The modern nurse operation with the TBK technique is to use the TBK technique documentation format for each patient each shift, operand notebook, and patient medical record